The Relationship between the General Budget Deficit and the Trade Balance - A Study of the Libyan Case - الدامي بدر, حسن (Dirasat in Economics and Business, 2026)
:The study aims to analysis the relationship between the general budget deficit and the Libya trade balance for the period from (1970-2020), as the study started from the Hypothesis that there is a causal relationship between the development of the general budget and the balance of trade balance, where the static tests of the tow variables were done, and the relationship was measured using the Error Correction Model and the Granger Causality Test, The results of the test showed a positive and causal effect of the trade balance deficit towards the general budget deficit.